2011
DOI: 10.1177/0950017011407971
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing the procurement of agency workers: the impact of vendor managed services in English social care

Abstract: In recent years marked changes have occurred in the way employers recruit and select agency workers, with this activity increasingly being outsourced to third party organizations providing 'vendor managed services' (VMS). Drawing on data from a study of English social services, this article explores the consequences of this outsourcing. The findings reveal that although VMS has delivered cost savings, it has also resulted in less effective placement matching, rising line manager workloads and concerns about se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Local authorities became block contract commissioners of employment agencies rather than acting as customers ‘shopping round’ to find possible stop‐gap social workers. Indications from this study suggest that managed vendor schemes have been easy to adopt and may have contributed to reduced costs, as Hoque et al. (2011) also observed.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Local authorities became block contract commissioners of employment agencies rather than acting as customers ‘shopping round’ to find possible stop‐gap social workers. Indications from this study suggest that managed vendor schemes have been easy to adopt and may have contributed to reduced costs, as Hoque et al. (2011) also observed.…”
Section: Resultssupporting
confidence: 70%
“…Local authorities became block contract commissioners of employment agencies rather than acting as customers 'shopping round' to find possible stop-gap social workers. Indications from this study suggest that managed vendor schemes have been easy to adopt and may have contributed to reduced costs, as Hoque et al (2011) also observed. Social workers and other stakeholders may be pleased to learn that, for a variety of reasons, the 'quick fix' of taking on and then getting rid of agency social workers is being subject to scrutiny in these challenging financial times.…”
Section: Resultssupporting
confidence: 70%
“…Over the course of the last three decades this industry has expanded significantly and has come to play an important role in the facilitation of sourcing skilled workers (nationally and internationally) to satisfy the demands of the host country labour market Forde, 2008;Forde and Mackenzie 2011;Gonos, 1997;Hoque et. al.…”
Section: Phase 2: Allocation and Labour Market Entry/navigationmentioning
confidence: 99%
“…Contextual similarities can be drawn with the work on labour market intermediaries Forde, 2008;Gonos, 1997;Hoque et. al.…”
mentioning
confidence: 99%
“…However, rather than seeing agency working as a solution to problems of workforce mobility, suffi ciency and quality, the previous UK Labour Government cast it as a problem in the public sector. It advised (Department of Health/Department for Education and Skills, 2006; Department of Health, 2009) local authorities to review the proportion of their expenditure on agency workers, including social workers, as way of controlling expenditure (see Hoque et al, 2011). This was accompanied by concern that the quality of work undertaken by temporary members of staff might not always be suffi cient, with arguments from some researchers that agency working itself poses risks to service users (Carey, 2008).…”
Section: Introductionmentioning
confidence: 99%